Didactic activities and the speaking skill in 8th grade EGB students at Unidad Educativa Particular Jean Piaget, school year 2019-2020 - Correa Caicedo, Roxanna Gissella (2020)
The speaking skill is considered the most important skill in language learning, because it is through the use of this skill that oral communication is produced. Mastering speaking in any foreign language requires time and dedication. In English language this is not an exception, and it is an aspect that many students usually need to improve in language learning. For this reason, English teachers have an important role in the learning process, as they have the responsibility to provide students opportunities to practice their speaking with the use of real language, either inside or outside the classroom. At “Unidad Educativa Jean Piaget”, 8th grade EGB students in the school year 2019-2020 have difficulties to communicate and express their ideas orally, even in the case of those students with good command of this second language. The current study addresses the need to develop the speaking skill in students of English as a second language, who face problems to express their ideas effectively, and proposes elements to enhance it, so learners can have the ability to communicate at least comprehensibly…………